2021
DOI: 10.1073/pnas.2012191118
|View full text |Cite|
|
Sign up to set email alerts
|

Screening for gene expression fluctuations reveals latency-promoting agents of HIV

Abstract: Upon treatment removal, spontaneous reactivation of latently infected T cells remains a major barrier toward curing HIV. Therapies that reactivate and clear the latent reservoir are only partially effective, while latency-promoting agents (LPAs) used to suppress reactivation and stabilize latency are understudied and lack diversity in their mechanisms of action. Here, we identify additional LPAs using a screen for gene-expression fluctuations (or “noise”) that drive cell-fate specification and control HIV reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…All flow cytometry data were analyzed using FCS Express 6 (Figure S2). A gate for JLat or TLat reactivation in the side scatter vs. fluorescein isothiocyanate (FITC) scatter plot was created using the untreated measurement similar to previous reports [6,20].…”
Section: Flow Cytometry Analyses and Gating Strategymentioning
confidence: 99%
See 3 more Smart Citations
“…All flow cytometry data were analyzed using FCS Express 6 (Figure S2). A gate for JLat or TLat reactivation in the side scatter vs. fluorescein isothiocyanate (FITC) scatter plot was created using the untreated measurement similar to previous reports [6,20].…”
Section: Flow Cytometry Analyses and Gating Strategymentioning
confidence: 99%
“…Excess over Bliss (EoB) scores were calculated for each treatment to determine whether a drug's interaction with TNF is additive or non-additive [6,9,22]. The EoB is defined as the difference between the observed combined effect and the expected combined effect:…”
Section: Bliss Independence Score Calculationmentioning
confidence: 99%
See 2 more Smart Citations
“…Reactivation of latent HIV in JLat 9.2 cells (Jordan et al, 2003) was previously studied using flow cytometry (Bohn-Wippert et al, 2017;Dar et al, 2014;Lu et al, 2021) and fluorescence microscopy (Bohn-Wippert et al, 2018), both using fluorescent probes expressed along with the viral genome. In a previous study (Bohn-Wippert et al, 2018), it was reported that reactivation occurred in cells with larger diameter.…”
Section: Glim Imagingmentioning
confidence: 99%